DEVELOPMENT OF RELIGIOUS MODERATION IN NORTH SUMATERA COMMUNITIES BY STRENGTHENING CROSSCULTURAL COMMUNICATION BASED ON LOCAL WISDOM VALUES - Mailin, Mailin; Sazali, Hasan; Dharma, Suhesti Wira (Al-Qalam, 2023)
The application of religious moderation using a cultural approach and local wisdom is very necessary because of the multicultural conditions of the North Sumatera region then there was the ambush of modernization and the presence of global culture hegemony. While the cultural approach and local wisdom can be done by using cross-cultural communication to avoid conflicts between different cultural groups And also maintain harmony between cultural groups. Â This study aims to determine the understanding of the people of North Sumatra on religious moderation and to find out the local wisdom that exists in the people of North Sumatra in line or not with the concept of religious moderation. This research uses qualitative methods with a descriptive approach, data wascollected using unstructured interviews and documentation. The determination of informants is carried out using purposive sampling techniques. The data analysis process is carried out by reducing data, presenting data and verifying. The results of the research showed that the people of North Sumatera Utara understand religious moderation through tolerance and harmony among religious people and among the values of local wisdom that exist in the people of North Sumatera is in line with the concept of religious moderation pioneered by the Ministry of Religious Affairs of the Republic of Indonesia, this has beeb proven by the culture that exists in North Sumatera since a long time ago has embraced an attitude of tolerance and harmony in carrying out daily life so as to create a harmonious relationship among the existing diversity.